Men and women trainers equally effective at promoting exercise adherence, self-efficacy, and fitness in women - Dunn-Lewis, C.; Dell'aquila, M. P.; Flanagan, S. D. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: This study examined the effect of a personal trainer`s sex on self-efficacy and fitness in woman clients. METHODS: Women (N.=28; mean age, 41.6±15.0 years; height, 153.49±28.11 cm; BMI, 25.9±6.4 kg/m2) completed a perceptual scale of self-efficacy (BARSE) and fitness tests before and after a training program. Trainers (men and women) met one-on-one with the volunteers on a biweekly basis for 8 weeks. Univariate analyses of change scores and repeated measures analysis of variance with Fisher`s LSD pairwise comparisons tested changes in dependent variables by trainer sex. RESULTS: Significant increases were seen in (mean±SE; change for men trainers; change for woman trainers): self-efficacy (7.3±3.4; 7.3±2.7%); leg press strength (18.2±3.7; 16.4±3.3 kg); seated row (6.1±1.5; 5.3±1.3 kg); muscular endurance in 60° flexion hold (20.5±5.8; 24.8±5.0 s) and wall-sit (19.9±6.4; 33.5±5.8 s); but not flexibility (V-sit, 7.11±5.51; 4.23±4.50 cm). Chest press strength significantly increased for women trainers only (2.7±2.2; 5.3±1.8 kg). Despite this, there were no significant differences for any variable in the change from pre-to-post based on the sex of the trainer. CONCLUSIONS: Both men and woman-led training was effective for increasing markers of self-efficacy and fitness in woman clients.